The dissemination of antimicrobial resistance determinants in the environment through horizontal gene transfer. (c2019) - Moussa, Jennifer J. (2019)
The extensive use of antibiotics led to the rise and dissemination of antibiotic-resistant bacteria. One of the most important factors facilitating the spread of resistance determinants is mobile genetic elements. Understanding the mechanisms associated with their circulation in the environment is essential to public health. The prevalence of antibiotic-resistant bacteria in surface water is a growing concern. We aimed at studying and defining the role of mobile genetic elements, particularly that of plasmids, in the propagation of resistance determinants in non-clinical environments. Water samples were collected from El Qa’a refugee camp and five major rivers in Lebanon. All collected samples were diluted and inoculated on MacConkey agar. The recovered isolates (n=91) were tested using the Kirby-Bauer disc diffusion assay. Multidrug-resistant (MDR) isolates were further characterized using whole-genome sequencing (WGS), pulse-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST). Escherichia coli (36/91) and Klebsiella pneumoniae (11/91) were the most common among the recovered isolates. In silico plasmid analysis was performed and validated using PCR-based replicon typing (PBRT) to identify and confirm incompatibility groups. Isolates from El Qa’a refugee camp were diverse and multidrug-resistant (MDR), with a multi-replicon blaNDM-5 positive E. coli being recovered from the site. blaCTX-M-15 and blaTEM-1B were also detected in the majority of the MDR isolates. Different ST types were identified including five isolates from Saida, Zahle, Beirut and El Qa’a belonging to the highly virulent E. coli ST131 phylogroup B2 and serotype O25: H4b. In this study, we determined the role of antibiotic resistance determinants in the contamination of water supplies in Lebanon. Our results showed a common occurrence of bacterial contaminants in surface water including ESBL- and carbapenemase-producing Enterobacteriaceae and an increase in the risk of resistance genes dissemination with the rise in the human population, population mobility and widespread lack of wastewater treatment.